PENGARUH PERMAINAN SUCKER BALL DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN GURUN PANJANG KECAMATAN BAYANG KABUPATEN PESISIRSELATAN TAHUN PELAJARAN 2012/2013 - Hartati, Rini; Putra, Atus Amadi; Anggraini, Villia (Pendidikan Matematika, 2013)
Â The background of this research is the low understanding of mathematical concept and study enthusiasm of VIII grade students of MTsN Gurun Panjang. This research is purposed to find out that the studentâs mathematical concept with Sucker Ball game along with handout is better than students mathematical concept with conventional learning in VIII grade students of MTsN Gurun Panjang year 2012/2013. The type of this research is experimental research, with research design random to the subject. The population in this research is VIII grade students of MTsN Gurun Panjang years 2012/2013 which is consist of three classes. The sampling technique is random, the class is VIII.1 class, and the control class is VIII.2 class. The instrumentation of this research is mathematical concept understanding test. The form of the test is essay. The data analysis technique is t- examination which is supported by Minitab software. Be based on the data analysis was known that both of the sample class have the normal distribution and the homogeneity at Â level. The result of hypotheses is P-value = 0,000 is lower than, so the hypotheses of this research are accepted. It can be conluded the matematical concept of students who implemented the Sucker Ball game along with handout is better than the mathematical concept of students who implimen hte conventional learning is VIII grade of MTsN Gurun Panjang, years 2012/2013.